A newer approach for the serodiagnosis of leptospirosis using outer membrane proteins of leptospira interrogans serovar tarassovi - Premlatha, MM; Kaur, IR; Avasthi, R; Dey, AB; Chaudhry, R (Asian Journal of Medical Sciences, 2013)
Objective: Leptospirosis in humans occurs throughout the world as an acute infection ranging imperceptible to severe, potentially fatal, renal and liver failure accompanied by haemorrhage and jaundice. In India, according to number of reports, Leptospirosis has been a significant health problem since 1980. This disease mimics influenza, hepatitis, dengue owing to which it often goes undiagnosed due to lack of awareness and diagnostic facilities in most of the laboratories in the country. This study was undertaken to diagnose suspected cases of Leptospirosis by IgM ELISA, DRIDOT and MAT, and also to standardize an in house IgM ELISA using OMP antigens of the L.tarassovi the predominant serovar in the study Materials & Methods: Blood samples were collected from a total of 287 patients (186 male and 101 female) presenting with acute febrile illness and fulfilling the criteria of clinical diagnosis of Leptospirosis. All the samples & healthy controls were subjected to ELISA (IgM serion), dridot, MAT, and Leptospira serovar Tarassovi OMP IgM ELISA, and for isolation of Leptospira. Results: IgM antibody could be detected by ELISA, Dridot and OMP ELISA of L. Tarassovi from Group I and Group II sera samples. It was observed by MAT that L.Tarassovi was the predominant serovar followed by L.australis, L.autumnalis, L.sejroe, L.pyrogenes, L.ballum, L.canicola, L.icterocopenhageni, L.cynopteri. A total of 5 isolates were recovered from Group I patients. Conclusion: IgM ELISA using sarcosyl extracted OMP antigens of serovar Tarassovi when compared with MAT the overall sensitivity and specificity was 72% and 81% respectively. The same sera reacted with serovar Australis, serovar Tarassovi, serovar Sejroe, serovar Pyrogenes, serovar Ballum and serovar Icterocopenhageni in MAT. DOI: http://dx.doi.org/10.3126/ajms.v4i2.6693 Asian Journal of Medical Sciences 4(2013) 41-46